Levels of CEA and Ca 19 - 9 in the sera and peritoneal cavity in patients with gastric and pancreatic cancers - Hoskovec, David; Varga, Jozef; Konečná, Ellen; Antos, Frantisek (Acta cirurgica brasileira, 2012)
PURPOSE: Tumor markers are substances found in blood and other biological fluids if tumor is present in the body. They can be produced by tumor itself or can be results of cancer - body relation. They may be used in the follow-up of cancer patients to identify tumor recurrence. Pre-treatment levels have prognostic tool and could signalize persistence of minimal residual disease despite radical surgery. METHODS: We operated on 52 patients with upper GI malignancy (32 with gastric cancer and 20 with pancreatic cancer). Blood samples were taken before surgery and peritoneal samples immediately after laparotomy before any manipulation with tumor. All samples were examined by standard biochemical technique and the level was compared with a stage of the disease. RESULTS: Patients suffering from gastric carcinoma of stage I and II had higher level of both markers in sera then in the peritoneal cavity, however most of them were within physiological range. Patients in stage III and IV had average marker levels in the peritoneal cavity higher than in sera. Number of positive findings was increasing according to the stage of the disease. The peritoneal levels of both markers varied extremely in higher stages. In patients suffering from pancreatic carcinoma the CEA levels both in sera and peritoneal cavity were parallel but peritoneal levels were slightly higher in stages III and IV. Ca 19 - 9 was more sensitive for pancreatic cancer. The percentage of positive findings was higher in sera but the level of Ca 19 - 9 was higher in the peritoneal cavity. The number of positive findings again correlated with the stage of the disease. CONCLUSIONS: Levels of tumor markers in sera could signalize inoperability of tumor (Ca 19 - 9 in cases of pancreatic carcinoma); peritoneal levels could predict R1 resection especially in gastric cancer patients and risk of early peritoneal recurrence of the disease. Difference between the levels in the peritoneum and sera may signalize the route of dissemination (hematogenous and intraperitoneal).
Keywords: dospělí; peritoneální dutina; Female; karcinoembryonální antigen; antigen CA-19-9; Carcinoembryonic Antigen; Adult; ženské pohlaví; Neoplasm Recurrence, Local; Pancreatic Neoplasms; Peritoneal Neoplasms; lidé; staging nádorů; nádory slinivky břišní; Stomach Neoplasms; Peritoneal Cavity; Male; Aged; peritoneální nádory; nádory žaludku; lokální recidiva nádoru; Peritoneal Lavage; CA-19-9 Antigen; lidé středního věku; peritoneální výplach; senioři; mužské pohlaví; Middle Aged; Neoplasm Staging; Humans